(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
In the present paper seeks to explain the change process undertaken by the Mexican highland agricultural producers organizations, that as a sign of this global phenomenon in which groups of agricultural producers have had to make adjustments and changes to the way Traditional production through the introduction of technology, quality control, commercial networks and the structure of the organization, becoming agribusiness organizations, able to adapt to political and economic rules derived from the processes of globalization and internationalization, this means successful strategies to ensure their survival, making the integration of local resources to the global rules of the game. Likewise, this transformation is presented as not only mark changes within the organization and within the local, but is involved in the development of the region. This is a qualitative, ethnographic and comparative study conducted in three agro-industries that have made this change process successfully.